Characterizing potential pathogens from intracellular bacterial community of protists in wastewater treatment plants. (January 2023) - Li, Li-Juan; Lin, Chenshuo; Huang, Xin-Rong; An, Xin-Li; Li, Wen-Jing; Su, Jian-Qiang; Zhu, Yong-Guan
Graphical abstract: Highlights: Protists can act as a shelter for pathogens to escape the adverse environment. Effluents harbor more bacterial pathogens carried by protists compared to influents. Protists in effluents from WWTPs can be a potential source of bacterial pathogens. Abstract: Protists are a trophically diverse and biogeochemically significant component of water environments and are widely reported as hosts of bacteria. However, the potential role of protists in wastewater treatment plants (WWTPs) as reservoirs for human pathogens does not appear to have received adequate attention. Here, a combination of fluorescence-activated cell sorting and Illumina sequencing was applied to characterize the dynamics of the internalized bacterial community of the enriched protists from the influents and effluents of five WWTPs. The results showed that Proteobacteria (mainly Betaproteobacteria) dominate the intracellular bacterial communities of protists in both influents and effluents of WWTPs, accounting for 72.6% of the total intracellular bacterial communities. The most frequently detected genus was Sulfuricurvum in the influent samples, Chryseobacterium and Pseudomonas were most prevalent in the effluent samples. Compared with the influents, a more diverse and abundant intracellular bacterial community was observed in the effluents. Moreover, the potential intracellular bacterial pathogens were 26 times higher in effluents than in influents, with Pseudomonas fluorescens and Pseudomonas putida significantly enriched in effluents. This work provides insights into the dynamics of bacterial communities and potential pathogens harbored by protists in the influents and effluents from WWTPs, contributing to the improved evaluation of biosafety in WWTPs.